Quantitative evaluation of the spinal cord compression in patients with cervical spondylotic myelopathy using synthetic MRI - Liu, Qiufeng; Shao, Haoyue; Liu, Chaoxu; Liu, Weiyin Vivian; Saeed, Azzam; Zhang, Qiya; Lu, Jun; Zhang, Guiling; Li, Li; Tang, Xiangyu; Du, Guanghui; Zhu, Wenzhen (Frontiers in Physiology, 2023)
Objectives: This work aimed to investigate the feasibility and diagnostic value of synthetic MRI, including T1, T2 and PD values in determining the severity of cervical spondylotic myelopathy (CSM). Methods: All subjects (51 CSM patients and 9 healthy controls) underwent synthetic MRI scan on a 3.0T GE MR scanner. The cervical canal stenosis degree of subjects was graded 0 – III based on the method of a MRI grading system. Regions of interest (ROIs) were manually drawn at the maximal compression level (MCL) by covering the whole spinal cord to generate T1MCL, T2MCL, and PDMCL values in grade I-III groups. Besides, anteroposterior (AP) and transverse (Trans) diameters of the spinal cord at MCL were measured in grade II and grade III groups, and relative values were calculated as follows: rAP = APMCL/APnormal, rTrans = TransMCL/Transnormal. rMIN = rAP/rTrans. Results: T1MCL value showed a decreasing trend with severity of grades (from grade 0 to grade II, P<0.05), while it increased dramatically at grade III. T2MCL value showed no significant difference among grade groups (from grade 0 to grade II), while it increased dramatically at grade III compared to grade II (P<0.05). PDMCL value showed no statistical difference among all grade groups. rMIN of grade III was significantly lower than that of grade II (P<0.05). T2MCL value was negatively correlated with rMIN, whereas positively correlated with rTrans. Conclusion: Synthetic MRI can provide not only multiple contrast images but also quantitative mapping, which is showed promisingly to be a reliable and efficient method in the quantitative diagnosis of CSM.